Health service utilisation during the COVID-19 pandemic in sub-Saharan Africa in 2020: a multicountry empirical assessment with a focus on maternal, newborn and child health services. Issue 5 (2nd May 2022) - Amouzou, Agbessi; Maïga, Abdoulaye; Faye, Cheikh Mbacké; Chakwera, Samuel; Melesse, Dessalegn Y; Mutua, Martin Kavao; Thiam, Sokhna; Abdoulaye, Idrissa Boukary; Afagbedzi, Seth Kwaku; Ag Iknane, Akory; Ake-Tano, Odile Sassor; Akinyemi, Joshua O; et al.
Abstract : Introduction: There are concerns about the impact of the COVID-19 pandemic on the continuation of essential health services in sub-Saharan Africa. Through the Countdown to 2030 for Women's, Children's and Adolescents' Health country collaborations, analysts from country and global public health institutions and ministries of health assessed the trends in selected services for maternal, newborn and child health, general service utilisation. Methods: Monthly routine health facility data by district for the period 2017–2020 were compiled by 12 country teams and adjusted after extensive quality assessments. Mixed effects linear regressions were used to estimate the size of any change in service utilisation for each month from March to December 2020 and for the whole COVID-19 period in 2020. Results: The completeness of reporting of health facilities was high in 2020 (median of 12 countries, 96% national and 91% of districts ≥90%), higher than in the preceding years and extreme outliers were few. The country median reduction in utilisation of nine health services for the whole period March–December 2020 was 3.9% (range: −8.2 to 2.4). The greatest reductions were observed for inpatient admissions (median=−17.0%) and outpatient admissions (median=−7.1%), while antenatal, delivery care and immunisation services generally had smaller reductions (median from −2% to −6%). Eastern African countries had greater reductions than those in West Africa, and rural districts were slightly more affected than urban districts. The greatest drop in services was observed for March–June 2020 for general services, when the response was strongest as measured by a stringency index. Conclusion: The district health facility reports provide a solid basis for trend assessment after extensive data quality assessment and adjustment. Even the modest negative impact on service utilisation observed in most countries will require major efforts, supported by the international partners, to maintain progress towards the SDG health targets by 2030.